Role of Community Pharmacists in Optimizing Opioid Therapy for Chronic Non-malignant Pain Patients in Pakistan - Iqbal, Ayesha (2023)
Background Chronic Non-Malignant Pain (CNMP) is one of the most common conditions in both high-income countries (HICs) and low middle-income countries (LMICs). CNMP can have a substantial impact on people, communities and puts an economic burden on the society. Opioids are commonly used worldwide for CNMP management. However, their use might have contributed to opioid use-related harm and increased mortality. There have been substantial reports of opioid diversion and misuse in Pakistan. Community pharmacists (CPs) might be able to help optimise the use of opioids in CNMP management but there is no regularised CP-based patient-centred services in Pakistan. Aim and objectives The aim of the study was to explore the potential role of CPs in opioid optimisation in people with CNMP in Pakistan. Objectives of this study included systematically exploring the role of CPs in opioid optimisation in CNMP management, exploring the current use of opioids in Pakistan and identify the role CPs can play to optimise the use of opioids in people with CNMP and explore factors that might influence the development and delivery of role of CPs in an opioid optimisation service. Methodology Conceptual guiding framework The UK Medical Research Council (MRC) guidelines for complex interventions was used as conceptual guiding framework for exploring the aim of this study. The data was collected in two phases: Phase 1: Systematic review The systematic review followed the 27-item PRISMA guidelines and studies between January 1990-June 2020 were included. All studies where pharmacists in ambulatory care settings helped in optimisation of opioids in the treatment of CNMP, as individuals or as part of a team were included and were descriptively synthesized. Phase 2: In-depth qualitative methods (Interviews, focus groups and case studies) Two studies were conducted to collect the data. The first study constituted of semi-structured interviews and focus groups from four stakeholder groups: pharmacy policy makers, people with CNMP, doctors and CPs. The second study included non-participant multiple case study observations in six community pharmacies. The data in phase two was collected from November 2019–December 2020. Data analysis Interviews and focus groups with all stakeholders in phase two were inductively analysed using reflexive thematic analysis using N-Vivo 12. For case studies, reflexive thematic analysis as well a cross case synthesis method using explanation building technique was used to analyse the data across six cases. Data triangulation Findings from both studies in phase two were triangulated using two steps; comparing, and categorising. Any code or subtheme about a particular phenomenon or a theme across both studies were brought together using one sheet one paper data visualisation technique. Diagrammatic model development Schematic diagrammatic models were developed in this thesis usual process mapping data visualisation technique. This was done selecting and representing events and situating data in time/process meaningfully. Results In this study 98 stakeholders participated (38 females). A total of 240 hours (40 hours/case) were observed during a six-week period of non-participant observational case studies in six community pharmacies. Phase 1: Systematic review In the systematic review 14 studies were included in the final data synthesis (total number of participants n=1175). Interventions by pharmacists decreased opioid dose in four studies and improved patient opioid safety in five studies. Qualitative studies showed positive perception of stakeholders for the development of CP role in optimisation of opioid therapy for people with CNMP. No actual interventions involving CPs or studies form LMICs were identified. Phase 2: Focus groups, interviews and case studies These studies were able to identify reasons contributing towards the non-availability of opioids, factors contributing towards the unsafe use of opioids and certain actions that can be taken by CPs to overcome existing barriers contributing to the unsafe use of opioids and help optimise their use. These studies also highlight advantages and benefits of developing the role of CPs in optimising opioid use in people with CNMP. In addition, these studies identified multiple level barriers and facilitators for the development and delivery of CP opioid service. They also helped identify strategies to overcome the perceived barriers and to leverage the facilitators in order to develop and deliver an opioid service. Data visualisation helped develop diagrammatic models after triangulation. Firstly, a logic model was developed that identifies the possible actions that can be undertaken by CPs to help overcome the barriers causing/contributing towards unsafe use of opioids. Secondly a CP proposed opioid service model was developed, tailored to the health system of Pakistan, that is anticipated to help optimise the use of opioids in people with CNMP. Finally, a CP opioid service logic model was developed that shows strategies perceived to develop and improve the capability of CPs to deliver the opioid service and help optimise the use of opioids. Conclusion This thesis explored the process, the need and service delivery of CP role in opioid optimisation. This thesis identified factors contributing towards unsafe use of opioids (logic model), what can be done by CPs to help people use opioids in an optimised manner (CP proposed service model), what challenges might CPs face while delivering the service and what can be done to improve the development and delivery of a CP opioid service for people with CNMP using opioids (CP service logic model). The findings provide policy makers with possible steps and actions that may be followed to facilitate the development and delivery of a CP service for opioid optimisation in Pakistan.